MISKONSEPSI SISWA MENGENAI STOMATA DAN FUNGSINYA DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR: analisis miskonsepsi konsep fotosintesis kelas V SD - Diana febryanti; Dr. Ghullam Hamdu M.pd.; Agnestasia Ramadhani Putri M.Pd. (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Misconceptions are one of the main obstacles in the science learning process at the elementary school level. One topic that is often misunderstood by students is the structure and function of stomata in plants. This study aims to identify and analyze the form of students' misconceptions about stomata and their functions in science subjects. The study was conducted on fifth grade elementary school students through video-based essay questions that describe parts of plants. The results showed that most students did not understand the function of stomata as a place for gas exchange and water evaporation. In contrast, many students consider stomata as a pathway for water or food to enter. This finding shows the importance of a more contextual and visual learning approach in understanding the concept of plant structure and function.